Preparation and testing of low-cost bioadsorbents for improving the anaerobic digestion of post-hydrothermal liquefaction wastewater (PHWW). Issue 5 (October 2022) - Sapillado, Gilda; de Melo, Mariza P.; Sobral, Paulo J.A.; Ribeiro, Rogers; Tommaso, Giovana
Abstract: There are currently several promising technologies for the removal of toxic compounds from wastewater; most of them are expensive or require sophisticated equipment. Thus, this study proposes that peanut shells be used as low-cost bioadsorbents for the removal of organic matter (COD) and ammoniacal nitrogen (NH4 + -N) from Spirulina hydrothermal liquefaction wastewater (PHWW). Additionally, anaerobic digestion (AD) was used as a biological treatment for pretreated PHWW (by adsorption) to promote additional organic matter removal while recovering energy in the form of methane. In this way, native (PB) and modified (APB) forms of peanut shell bioadsorbents were investigated. APB was activated using NaOH and HCl. For comparison, granular activated carbon (GAC) was chosen as the standard. The adsorbate-PHWW was obtained by using 20% solids (w/v) in the hydrothermal liquefaction (HTL) of Spirulina at 260 °C for 60 min. Response surface methodology (RSM) was used to explore and optimize the effect of various adsorption parameters, such as temperature, pH, and adsorbent dosage. Biochemical potential (BMP) tests were conducted under mesophilic conditions. In adsorption assays, PB was found to be more efficient at removing NH4 + -N, while APB and GAC achieve higher COD removal percentages. In comparison to untreated PHWW, bioadsorption promoted higher efficiency phenol removal and COD conversion to methane during BMP tests. The anaerobic processes that followed APB and PB adsorption significantly removed more COD than the process fed with GAC-pretreated PHWW. These results established the feasibility of using peanut shells as bioadsorbents in the pretreatment of PHWW, which resulted in an increase in biogas/methane yield. Graphical Abstract: ga1 Highlights: Anaerobic digestion of post-hydrothermal liquefaction wastewater (PHWW) was studied. Peanut shells were used as bioadsorbent in the pretreatment of PHWW. Chemical activation improved physicochemical characteristics of the bioadsorbents. The effect of temperature, pH and adsorbent dosage was optimized using response surface methodology (RSM). Methane production rate was increased when bioadsorbents were used as pretreatment.